2017
DOI: 10.1155/2017/6894040
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Changes in the Kidney following Congestive Heart Failure by Volume Overload in Rats

Abstract: Background This study investigated histopathological changes and apoptotic factors that may be involved in the renal damage caused by congestive heart failure in a rat model of infrarenal aortocaval fistula (ACF). Methods Heart failure was induced using a modified approach of ACF in male Wistar rats. Sham-operated controls and ACF rats were characterized by their morphometric and hemodynamic parameters and investigated for their histopathological, ultrastructural, and apoptotic factor changes in the kidney. Re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Intriguingly, organ/body weight indices of the liver and kidney were not significantly altered in ACF rats which may be due to the large AV fistula itself that affects organ perfusion preventing it from increasing organ weight. Nonetheless, both organs showed overt histopathological changes in the liver [45] and kidney [46], as has been previously published. Secondly, this study was conducted to assess the indirect adverse opioidergic effects in cardiac volume overload.…”
Section: Discussionsupporting
confidence: 81%
“…Intriguingly, organ/body weight indices of the liver and kidney were not significantly altered in ACF rats which may be due to the large AV fistula itself that affects organ perfusion preventing it from increasing organ weight. Nonetheless, both organs showed overt histopathological changes in the liver [45] and kidney [46], as has been previously published. Secondly, this study was conducted to assess the indirect adverse opioidergic effects in cardiac volume overload.…”
Section: Discussionsupporting
confidence: 81%
“…CRS2 is defined as chronic cardiac insufficiency, leading to progressive manifestations of kidney damage, which contributes to the progression of CKD (155,156). Morphological studies in rat models of congestive HF-induced renal injury revealed mitochondrial swelling in renal tubular epithelial cells, possibly due to the release of Cyt-c, which mediated caspase 3 activation and nuclear transfer and triggered apoptosis, supporting the role of mitochondria-mediated apoptosis in CRS2 (145). Early empagliflozin treatment protects cardiac and renal function in CRS rats by reducing apoptin (mitochondrial-Bax/cleavedcaspase-3/cleaved-parp) and fibrosin (TGF-β/Smad3), reducing DNA/mitochondrial damage (γ-H2AX/cytoplasmic-Cyt-c), and maintaining mitochondrial function and integrity (146).…”
Section: Mitochondrial Dysfunction In Crs2mentioning
confidence: 84%
“…In this aspect, renal dysfunction induced by KBrO 3 in experimental animals characterized by tubular damage, loss of brush border, tubular necrosis, tubular dilatation, tubular cell swelling and glomerular injuries (Khan et al, 2010;Khan et al, 2012). Aboryag et al (2017) suggested that glomerular atrophy with widening of Bowman's space, epithelial shedding in tubular structures, pyknotic nuclei, desquamated cells, are indicators of apoptosis. This suggestion was confirmed in the present study by Tunnel assay which shows higher number of apoptotic cells in kidney of KBrO 3 treated rats.…”
Section: Discussionmentioning
confidence: 99%